AB0473 Work-related disability in takayasu's arteritis: a british series. (23rd January 2014) - Mehta, P.; Mason, J.
Abstract : Background: Takayasu's arteritis (TA) is an inflammatory disorder which is most active during working years, thus affecting productivity. Objectives: We aimed to survey the frequency and associated reasons of work-related disability amongst patients attending our tertiary referral TA centre and also how work may affect patients' health with respect to their Takayasu's arteritis. Methods: Approval was obtained from the Research Ethics committee. A postal questionnaire survey was sent to 90 patients attending our TA clinic. Consent was implied, by return of questionnaires. Results: 41 responses were received, 90% were female with a median age of 52 years. The median age at first symptoms was 34 years and at diagnosis of TA 38 years. 63% were White British. 12% had high-school education, 29% university degrees and 24% vocational qualifications. 29% were taking no medication, 59% steroids, 51% immunosuppressants and 2% TNF-blockers.10% considered themselves to have significant co-morbidities (all Crohn's disease). 17% were homemakers, 27% retired (55% of these were medically retired), 49% employed and 7% unemployed. 81% of the 21 patients currently not working, had been working before TA was diagnosed. 71% of these patients stated they were not working because of TA. The most common reasons for this were claudication (47%) and neurological symptoms/deficit (27%). 43% patients felt their TA had improved after stopping work. Of the 49% working, 70% were full-time and 30% part-time. 85% had made changes to their work because of TA – reduced hours (35%) and changed job (50%). 41% felt their TA had improved after these changes. The mean number of sick days was 5days/year, with 2 days attributed to TA. The mean visual analogue scale assessments for the effect of TA on productivity at work was 7.9, the effect of TA on regular activities was 6.78 and the effect of work on TA was 5.92. Conclusions: Work-related disability in TA is high and underappreciated. A large number of patients give up work or change their work practice because of TA. Claudication and neurological effects were the most common reasons given. The perceived effects of TA on productivity at work and the effects of work on patients' health are considerable. Disclosure of Interest: None Declared